2009
DOI: 10.1111/j.1464-410x.2009.08340.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth factors in hormone‐ and drug‐resistant prostate cancer cells by synergistic combination of docetaxel and octreotide

Abstract: caspase 3/7 activity were measured. We also investigated the effect of combined docetaxel and octreotide on growth factors secreted from prostate cancer cells using a human growth factor antibody array. RESULTSThe combination of docetaxel and octreotide resulted in significant synergistic cytotoxic activity and apoptosis, which was dose-and time-dependent. The combined treatment also resulted in significantly less secretion of stem cell factor and platelet-derived growth factor-AB in PC-3 cells, and transformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…PC3wt cells treated with the sequential schedule were more sensitive to cell death if docetaxel was given before octreotide, compared with docetaxel alone. This observation was similar to that obtained by Erten et al [27] showing a significant synergistic effect of the sequential treatment irrespective of which agent was given first. For PC3R cells, the stronger effect on cell proliferation was observed when the two drugs were given together 4 days after seeding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PC3wt cells treated with the sequential schedule were more sensitive to cell death if docetaxel was given before octreotide, compared with docetaxel alone. This observation was similar to that obtained by Erten et al [27] showing a significant synergistic effect of the sequential treatment irrespective of which agent was given first. For PC3R cells, the stronger effect on cell proliferation was observed when the two drugs were given together 4 days after seeding.…”
Section: Discussionsupporting
confidence: 92%
“…These results are also in agreement with data on hepatocellular carcinoma cell lines [26]. Our data are, however, not in agreement with the results obtained in prostate cancer cell lines by Erten et al [27], who reported that both docetaxel and octreotide decreased cell proliferation in a time-dependent and dose-dependent manner when using PC3wt and DU145 cells, indicating different roles of the two drugs on those cell lines.…”
Section: Discussionsupporting
confidence: 79%
“…28 In another study, the combination of Docetaxel and Octreotide significantly reduced the levels of FGF-β in human hormone and drug refractory prostate cancer cell lines. 29 In present study MMC, Octreotid and Tacrolimus equally decreased the FGF-β immunostaining intensity at the scleral flap region.…”
Section: Discussionsupporting
confidence: 62%
“…The relative amounts of mono and oligonucleosomes generated from the apoptotic cells were quantified using monoclonal antibodies directed against DNA and histones by ELISA. Detection of apoptosis was verified by measuring caspase 3/7 enzyme activity as described in our previous study (Erten et al 2009). It is of note to mention that caspase 3/7 enzyme activity was only measured in MDA-MB-231, since MCF-7 lack of caspase 3 enzyme.…”
Section: Sequential Treatmentmentioning
confidence: 99%